Nω-(Carboxymethyl)arginine Is One of the Dominant Advanced Glycation End Products in Glycated Collagens and Mouse Tissues. (10th September 2019) - Kinoshita, Sho; Mera, Katsumi; Ichikawa, Hiroko; Shimasaki, Satoko; Nagai, Mime; Taga, Yuki; Iijima, Katsumasa; Hattori, Shunji; Fujiwara, Yukio; Shirakawa, Jun-ichi; Nagai, Ryoji
Abstract : Advanced glycation end products (AGEs) accumulate in proteins during aging in humans. In particular, the AGE structure N ω -(carboxymethyl)arginine (CMA) is produced by oxidation in glycated collagen, accounting for one of the major proteins detected in biological samples. In this study, we investigated the mechanism by which CMA is generated in collagen and detected CMA in collagen-rich tissues. When various protein samples were incubated with glucose, the CMA content, detected using a monoclonal antibody, increased in a time-dependent manner only in glycated collagen, whereas the formation of N ε -(carboxymethyl)lysine (CML), a major antigenic AGE, was detected in all glycated proteins. Dominant CMA formation in glycated collagen was also observed by electrospray ionization-liquid chromatography-tandem mass spectrometry (LC-MS/MS). During incubation of glucose with collagen, CMA formation was enhanced with increasing glucose concentration, whereas it was inhibited in the presence of dicarbonyl-trapping reagents and a metal chelator. CMA formation was also observed upon incubating collagen with glyoxal, and CMA was generated in a time-dependent manner when glyoxal was incubated with type I–IV collagens. To identify hotspots of CMA formation, tryptic digests of glycated collagen were applied to an affinity column conjugated with anti-CMA. Several CMA peptides that are important for recognition by integrins were detected by LC-MS/MS and amino acid sequence analyses. CMA formation on each sequence was confirmed by incubation of the synthesized peptides with glyoxal and ribose. LC-MS detected CMA in the mouse skin at a higher level than other AGEs. Furthermore, CMA accumulation was greater in the human aorta of older individuals. Overall, our study provides evidence that CMA is a representative AGE structure that serves as a useful index to reflect the oxidation and glycation of collagen.